Evaluasi Keterampilan Kitabah (Menulis) Secara Komprehensif: Implikasi Portofolio Assesment dalam Keterampilan Kitabah - Zufa Al Husna; M. Yunus Abu Bakar (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Writing skill (Maharah al-Kitabah) is one of the productive competencies that plays a significant role in Arabic language learning. The evaluation of writing skills should not merely focus on the final written product but also consider the continuous development process of learners’ writing abilities. Therefore, an assessment model capable of measuring writing competence comprehensively and authentically is required. This paper aims to examine the implementation of portfolio assessment in evaluating Arabic writing skills, including its concepts, objectives, forms, implementation procedures, as well as its strengths and weaknesses. Portfolio assessment enables teachers to evaluate essential aspects of writing, such as grammatical accuracy (nahw and sarf), vocabulary usage, content organization, coherence and cohesion, creativity of ideas, and accuracy of spelling and punctuation. Through systematic collection of students’ work, selection of best works, self-reflection, and teacher feedback, portfolio assessment effectively documents students’ writing development in a more objective and sustainable manner. The findings indicate that portfolio assessment serves as an effective alternative for evaluating writing skills because it integrates both process-oriented and product-oriented assessment while encouraging active learner participation in the learning process